Structural Insights Support Targeting ASK1 Kinase for Therapeutic Interventions - Obsilova, Veronika; Honzejkova, Karolina; Obsil, Tomas (International journal of molecular sciences, 2021)
Apoptosis signal-regulating kinase (ASK) 1, a member of the mitogen-activated protein kinase kinase kinase (MAP3K) family, modulates diverse responses to oxidative and endoplasmic reticulum (ER) stress and calcium influx. As a crucial cellular stress sensor, ASK1 activates c-Jun N-terminal kinases (JNKs) and p38 MAPKs. Their excessive and sustained activation leads to cell death, inflammation and fibrosis in various tissues and is implicated in the development of many neurological disorders, such as Alzheimer's, Parkinson's and Huntington disease and amyotrophic lateral sclerosis, in addition to cardiovascular diseases, diabetes and cancer. However, currently available inhibitors of JNK and p38 kinases either lack efficacy or have undesirable side effects. Therefore, targeted inhibition of their upstream activator, ASK1, stands out as a promising therapeutic strategy for treating such severe pathological conditions. This review summarizes recent structural findings on ASK1 regulation and its role in various diseases, highlighting prospects for ASK1 inhibition in the treatment of these pathologies.
Keywords: MAP kinasový signální systém; Signal Transduction; proteiny regulující apoptózu; stres endoplazmatického retikula; Humans; MAP Kinase Kinase Kinases; ASK1; zvířata; MAP Kinase Signaling System; fosforylace; oxidační stres; signální transdukce; JNK Mitogen-Activated Protein Kinases; MAP kinasa-kinasa-kinasa 5; apoptóza; Protein Interaction Maps; phosphorylation; protein–protein interaction; JNK mitogenem aktivované proteinkinasy; MAP kinase; 14-3-3 Proteins; p38 Mitogen-Activated Protein Kinases; oxidace-redukce; Oxidative Stress; Phosphorylation; Apoptosis Regulatory Proteins; mitogenem aktivované proteinkinasy p38; Animals; kinase; lidé; MAP Kinase Kinase Kinase 5; mapy interakcí proteinů; Oxidation-Reduction; MAP kinasy kinas (kinas); Apoptosis; proteiny 14-3-3; 14-3-3; Endoplasmic Reticulum Stress